2019
DOI: 10.1002/alr.22400
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes and prognostic factors of squamous cell carcinomas arising from sinonasal inverted papillomas: a retrospective analysis of 120 patients

Abstract: Background:This study aimed to analyze the prognostic factors and survival outcomes of squamous cell carcinoma (SCC) originating from sinonasal inverted papillomas (IPs), based on data from a single institution. Methods:The data from 120 patients treated at the affiliated Beijing Tongren Hospital, Capital Medical University, for SCC originating from sinonasal IPs between 2005 and 2018 were retrospectively reviewed. Data related to demographic features, tumor characteristics, treatment modality, and clinical ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
(33 reference statements)
3
13
1
Order By: Relevance
“…Detection of tumors at an early stage is thus of utmost importance, and may have a significant prognostic advantage. Regarding surgical margins, our findings for this aspect are also in accordance with the findings from several studies, 14,27,28 which have shown positive margins to be associated with poor survival outcomes. However, the positive margin rate noted in our study was higher compared with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Detection of tumors at an early stage is thus of utmost importance, and may have a significant prognostic advantage. Regarding surgical margins, our findings for this aspect are also in accordance with the findings from several studies, 14,27,28 which have shown positive margins to be associated with poor survival outcomes. However, the positive margin rate noted in our study was higher compared with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…[18][19][20] Besides the risk of recurrence, there is also the risk of malignant transformation, which is seen in 5% to 11% of all specimens. 14,[21][22][23][24][25][26] Previous series reported a rate of approximately 2:1 of synchronous to metachronous transformation. 22 Treatment of SNIPs primarily consists of David Holzmann and Christian M. Meerwein contributed equally to this study and worked as joint last authors.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the risk of recurrence, there is also the risk of malignant transformation, which is seen in 5% to 11% of all specimens 14,21‐26 . Previous series reported a rate of approximately 2:1 of synchronous to metachronous transformation 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of IP associated with the synchronously or metachronous SCC is reported from 2% to 53% ( 2 5 ), in which synchronous SCC accounts for approximately 55%–70% ( 2 , 5 , 6 ). Therefore, it is essential for precision diagnosis and treatment as well as prognosis to accurately predict IP-SCC preoperatively ( 3 , 7 , 8 ). However, it is very difficult to diagnose IP-SCC preoperatively due to similarity in clinical presentation and imaging findings with IP ( 9 ).…”
Section: Introductionmentioning
confidence: 99%